Analytic and Heuristic Methodologies for Solving the Resource Constrained Project Scheduling Problem (RCPSP): a review Part 1 (2014)
This paper presents and describes the most relevant methods for the solution of the Resource Constrained Project Scheduling Problem, RCPSP. A critical review of the state of the art, based on the most signicant papers published in the academic literature